Direct and indirect parental exposure to endocrine disruptors and elevated temperature influences gene expression across generations in a euryhaline model fish - Bethany M. DeCourten; Richard E. Connon; Susanne M. Brander (PeerJ, 2019)
Aquatic organisms inhabiting polluted waterways face numerous adverse effects, including physiological disruption by endocrine disrupting compounds (EDCs). Little is known about how the temperatures associated with global climate change may influence the response of organisms exposed to EDCs, and the effects that these combined stressors may have on molecular endpoints such as gene expression. We exposed Menidia beryllina (inland silversides) to environmentally relevant concentrations (1 ng/L) of two estrogenic EDCs (bifenthrin and 17α-ethinylestradiol; EE2) at 22 °C and 28 °C. We conducted this experiment over multiple generations to better understand the potential effects to chronically exposed populations in the wild. We exposed adult parental fish (F0) for 14 days prior to spawning of the next generation. F1 larvae were then exposed from fertilization until 21 days post hatch (dph) before being transferred to clean water tanks. F1 larvae were reared to adulthood, then spawned in clean water to test for further effects of parental exposure on offspring (F2 generation). Gene expression was quantified by performing qPCR on F0 and F1 gonads, as well as F1 and F2 larvae. We did not detect any significant differences in the expression of genes measured in the parental or F1 adult gonads. We found that the 28 °C EE2 treatment significantly decreased the expression of nearly all genes measured in the F1 larvae. This pattern was transferred to the F2 generation for expression of the follicle-stimulating hormone receptor (FSHR) gene. Expression of 17β-hydroxysteroid dehydrogenase (17β-HSD) and G protein-coupled receptor 30 (GPR30) revealed changes not measured in the previous generation. Effects of the bifenthrin treatments were not observed until the F2 generation, which were exposed to the chemicals indirectly as germ cells. Our results indicate that effects of EDCs and their interactions with abiotic factors, may not be adequately represented by singular generation testing. These findings will contribute to the determination of the risk of EDC contamination to organisms inhabiting contaminated waterways under changing temperature regimes.